Taxonomic validation of a well-known Odontoglossum (Orchidaceae: Oncidiinae) “ghost” - Dalström, Stig (Lankesteriana: International Journal on Orchidology, 2014)
The plant that was first called “Odontoglossum wyattianum” by Gurney Wilson was exhibited at a meeting of the Royal Horticultural Society on January 3, 1928. No official description was ever published and no type specimen was ever designated, or has surfaced, hence making this distinct species a taxonomic ‘ghost’. The taxonomic validation of Odontoglossum wyattianum is made here through the designation of a holotype, together with a diagnosis, a brief taxonomic history and comparison with similar and closely related species.